Изменение теплопроводности контакта элементов лазерного гироскопа под действием прижимного усилия - Погорелов, Сергей Юрьевич; Счастливец, Кирилл Юрьевич; Марусенко, Светлана Ивановна (НТУ "ХПИ", 2007)
The measurement accuracy of ring laser gyros depends on temperature field parameters. In the proposed paper the influence of contact thermal conduction between the construction cover and laser gyroscope resonator including deformations depending on mechanical construction spring pretension was analyzed.
Keywords: навигационные комплексы; местоположение подвижного объекта; навигационная система; конвективная теплоотдача; термическое сопротивление; процессы теплопроводности